Ca2+ signalling in fibroblasts and the therapeutic potential of KCa3.1 channel blockers in fibrotic diseases. (3rd February 2020) - Roach, Katy M.; Bradding, Peter
Abstract : The role of Ca 2+ signalling in fibroblasts is of great interest in fibrosis‐related diseases. Intracellular free Ca 2+ ([Ca 2+ ]i ) is a ubiquitous secondary messenger, regulating a number of cellular functions such as secretion, metabolism, differentiation, proliferation and contraction. The intermediate conductance Ca 2+ ‐activated K + channel KCa 3.1 is pivotal in Ca 2+ signalling and plays a central role in fibroblast processes including cell activation, migration and proliferation through the regulation of cell membrane potential. Evidence from a number of approaches demonstrates that KCa 3.1 plays an important role in the development of many fibrotic diseases, including idiopathic pulmonary, renal tubulointerstitial fibrosis and cardiovascular disease. The KCa 3.1 selective blocker senicapoc was well tolerated in clinical trials for sickle cell disease, raising the possibility of rapid translation to the clinic for people suffering from pathological fibrosis. This review after analysing all the data, concludes that targeting KCa 3.1 should be a high priority for human fibrotic disease.